2021
DOI: 10.1002/pros.24118
|View full text |Cite
|
Sign up to set email alerts
|

Targeting backdoor androgen synthesis through AKR1C3 inhibition: A presurgical hormonal ablative neoadjuvant trial in high‐risk localized prostate cancer

Abstract: Background Localized prostate cancers (PCs) may resist neoadjuvant androgen receptor (AR)‐targeted therapies as a result of persistent intraprostatic androgens arising through upregulation of steroidogenic enzymes. Therefore, we sought to evaluate clinical effects of neoadjuvant indomethacin (Indo), which inhibits the steroidogenic enzyme AKR1C3, in addition to combinatorial anti‐androgen blockade, in men with high‐risk PC undergoing radical prostatectomy (RP). Methods This was an open label, single‐site, Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…After the screening, a full-text review of 30 articles was performed. According to our inclusion criteria, we finally identified 20 studies eligible for systematic review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Of the twenty studies, we identified eight phase II RCTs comparing the efficacy and/or safety of ARSI-based combination therapy versus other combinations or ADT/ARSI alone (Table 1) [13][14][15][16][17][18][19][20].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the screening, a full-text review of 30 articles was performed. According to our inclusion criteria, we finally identified 20 studies eligible for systematic review [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Of the twenty studies, we identified eight phase II RCTs comparing the efficacy and/or safety of ARSI-based combination therapy versus other combinations or ADT/ARSI alone (Table 1) [13][14][15][16][17][18][19][20].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Several studies assessing the efficacy of neoadjuvant ARSIs used a pathological endpoint as a surrogate for long-term oncological outcomes (Table 2 and Supplementary Tables S3 and S4) [13][14][15][17][18][19]21,22]. However, no consensus yet exists regarding the ideal definition of a pathological response following neoadjuvant hormonal therapy.…”
Section: Pathologic Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of two phase II trials suggested no improvement in rates of complete pathologic response or reduction in residual tumor in patients treated with apalutamide in addition to abiraterone and LHRH agonist (39,51). A single-arm Phase II trial reported pathologic features after 3-months of neoadjuvant apalutamide, abiraterone, degarelix and indomethacin prior to prostatectomy (53). The addition of indomethacin may further decrease production of testosterone by inhibiting AKR1C3.…”
Section: Neoadjuvant Hormonal Deprivation Novel Anti-androgensmentioning
confidence: 99%